Emergency department visits for psychiatric care during the first lockdown in Melbourne. (February 2022) - Jagadheesan, Karuppiah; Danivas, Vijay; Itrat, Annie; Lakra, Vinay
Objective: We investigated the nature of patients presenting to an emergency department (ED) during the first lockdown in Melbourne. Method: This study compared adult patients in the North West Area Mental Health Service catchment area who presented to the local ED during the lockdown (16 March–12 May 2020) and the control (16 March–12 May 2019) periods. Results: The control and lockdown periods included 321 and 332 patients, respectively. Compared to the control period, patients with non-English speaking backgrounds and presenting complaints of suicidal behaviour were lower, whereas patients with anxiety symptoms and needing compulsory assessments were higher in the lockdown period. Diagnostically, the lockdown period included more patients with anxiety disorders, substance use disorders and psychotic disorders. Conclusions: ED access for acute psychiatric care can vary depending upon certain patient characteristics during lockdowns.